THE DIGITAL PERSONAL DATA PROTECTION ACT OF 2023: : STRENGTHENING PRIVACY IN THE DIGITAL AGE - Saurabh, Shubham (International Journal of Law in Changing World, 2024)
The Digital Personal Data Protection Act of 2023 is a landmark piece of legislation that safeguards individual privacy rights and strengthens data security. It emphasizes the power of individuals over their personal data by introducing the concepts of consent, data minimization, and the right to be forgotten. The Act also impacts businesses by imposing obligations on data controllers and processors, requiring them to implement effective data protection frameworks and procedures. The Establishment of the Data Protection Board of India as the Central Watchdog will be crucial in enforcing the Act. This research paper examines the power given to people over their personal data and its impact on business compliance and operational changes on data controllers, given the penalties for non-compliance. The analysis concludes that the Digital Personal Data Protection Act of 2023 serves as a beacon for privacy rights and data protection in the digital world. __________ La Ley de Protección de Datos Personales Digitales de 2023 es una legislación histórica que protege los derechos de privacidad individual y refuerza la seguridad de los datos. Destaca el poder de las personas sobre sus datos personales mediante la introducción de conceptos como el consentimiento, la minimización de datos y el derecho al olvido. La Ley también afecta a las empresas al imponer obligaciones a los controladores y procesadores de datos, exigiéndoles implementar marcos y procedimientos efectivos de protección de datos. La creación de la Junta de Protección de Datos de la India como el organismo central de supervisión será crucial para la aplicación de la Ley. Este trabajo de investigación analiza el poder otorgado a las personas sobre sus datos personales y su impacto en el cumplimiento empresarial, así como los cambios operativos para los controladores de datos, dados los riesgos de sanciones por incumplimiento. El análisis concluye que la Ley de Protección de Datos Personales Digitales de 2023 se erige como un faro para los derechos de privacidad y la protección de datos en el mundo digital. __________ 《2023年数字个人数据保护法》是一部具有里程碑意义的法律，旨在保障个人隐私权并加强数据安全。通过引入同意、数据最小化和被遗忘权等概念，该法强调个人对其个人数据的掌控权。该法还对企业产生影响，要求数据控制者和处理者履行义务，实施有效的数据保护框架和程序。印度数据保护委员会的设立作为中央监管机构，对于推动该法的实施至关重要。本文研究了该法赋予个人的数据掌控权，以及其对企业合规性和数据控制者运营变革的影响，尤其是在违反规定的处罚风险下。分析得出结论，《2023年数字个人数据保护法》是数字世界中隐私权和数据保护的灯塔。